2018
DOI: 10.1029/2017ja025151
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Electrons on the Martian Nightside: Structure and Variability

Abstract: The precipitation of suprathermal electrons is the dominant external source of energy deposition and ionization in the Martian nightside upper atmosphere and ionosphere. We investigate the spatial patterns and variability of ionizing electrons from 115 to 600 km altitude on the Martian nightside, using CO 2 electron impact ionization frequency (EIIF) as our metric, examining more than 3 years of data collected in situ by the Mars Atmosphere and Volatile EvolutioN spacecraft. We characterize the behavior of EII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 59 publications
8
68
0
Order By: Relevance
“…In Figure , we also show the 1/ e edge values in CO 2 electron impact ionization for different geophysical conditions. The figure reveals the presence of north‐south asymmetry, compatible with previous calculations of the electron impact ionization efficiency based on both the MAVEN SWEA and Mars Global Surveyor Electron Reflectometer data (e.g., Lillis & Brain, ; Lillis et al, ). We expect such an asymmetry to be indicative of reduced electron precipitation over regions near strong magnetic anomalies, which are well known to cluster over the southern hemisphere of Mars (e.g., Connerney et al, ).…”
Section: Implications On Plasma Sourcessupporting
confidence: 88%
“…In Figure , we also show the 1/ e edge values in CO 2 electron impact ionization for different geophysical conditions. The figure reveals the presence of north‐south asymmetry, compatible with previous calculations of the electron impact ionization efficiency based on both the MAVEN SWEA and Mars Global Surveyor Electron Reflectometer data (e.g., Lillis & Brain, ; Lillis et al, ). We expect such an asymmetry to be indicative of reduced electron precipitation over regions near strong magnetic anomalies, which are well known to cluster over the southern hemisphere of Mars (e.g., Connerney et al, ).…”
Section: Implications On Plasma Sourcessupporting
confidence: 88%
“…It is not immediately apparent why increased ram pressure in the upstream solar wind would compress crustal fields on the nightside of the planet, but we believe that this effect is due to an associated increase in magnetic field strength in the Martian magnetotail. It has been demonstrated that an increase in solar wind pressure translates into increased magnetic pressure in the tail (e.g., Lillis et al, ), and we suggest that this causes the compression of nightside crustal fields and produces the topological trends shown here.…”
Section: Nightside Resultssupporting
confidence: 71%
“…Magnetic fields in the Martian space environment facilitate a complex interaction between the solar wind and the planet's ionosphere. By directing the flow of charged particles, they control the structure of energetic electron precipitation across Mars (Dubinin, Fraenz, Woch, Roussos, et al, 2008;Lillis & Brain, 2013;Lillis et al, 2009Lillis et al, , 2018Xu et al, 2014). These electrons enter the atmosphere and impart energy, leading to impact ionization (Fillingim et al, 2010(Fillingim et al, , 2007Lillis & Fang, 2015;Lillis et al, 2011;Němec et al, 2011), local heating (Fox & Dalgarno, 1979;Krymskii et al, 2004;Sakai et al, 2016), and the production of aurora (Brain et al, 2006;Haider et al, 1992;Leblanc et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The nightside defined in the present study is restricted to SZA >120° where day‐to‐night plasma transport is negligible and surpassed by SW electron precipitation (e.g., Cui et al, ; Němec et al, ; Withers et al, ). As a consequence, the nightside ionosphere is patchy and closely modulated by the ambient magnetic field configuration (e.g., Lillis & Brain, ; Lillis & Fang, ; Lillis et al, , , ). Recently, Xu, Mitchell, Liemohn, et al () obtained the magnetic topology mappings on both the dayside and the nightside of Mars with the aid of the electron pitch angle distribution measured by the MAVEN Solar Wind Electron Analyzer.…”
Section: Discussionmentioning
confidence: 99%
“…Energetic electron depletion is frequently seen on the nightside of Mars indicative of closed field lines effectively shielding the precipitation of SW electrons (e.g., Steckiewicz et al, , ), and such regions are preferentially located near strong crustal anomalies (Xu, Mitchell, Liemohn, et al, ). The incident electron flux also increases as the field lines are more vertical (Lillis & Brain, ; Lillis et al, ), which is responsible for the apparent correlation between magnetic orientation and ionospheric electron content as revealed by the MEx MARSIS data (Safaeinili et al, ).…”
Section: Introductionmentioning
confidence: 99%